The Effect of Dosage, Number of Pesticides, Personal Protective Equipment Usage, Direction, Time, Duration and Spraying Frequency of Kolinesterase Content on Farmers in Gawu-Gawu Bouso Village North Gunungsitoli Sub-District, Gunungsitoli City - Eva Valentine Br. Hotang; Taufik Ashar; Wirsal Hasan (Budapest International Research and Critics University, 2020)
Pesticide poisoning occurs when there is a certain amount of pesticide material that reaches and / or enters the body. Pesticide poisoning is influenced by many factors including dose, amount, time, length, direction and frequency of spray. This study was an observational study using a cross sectional design that aims to determine the effect of dosage, amount of pesticides, PPE usage, direction, time, duration and frequency of spraying on the level of cholesteresterase farmers in Gawu-Gawu Bouso Village, Gunungsitoli Utara District, Gunungsitoli City. The population includes farmers and farm laborers who spray pesticides in Gawu-Gawu Bouso Village, Gunungsitoli Utara District with 44 research samples. Data analysis uses univariate, bivariate (chi-square test) and multivariate analysis with logistic regression. The results of the bivariate analysis showed that there were 6 independent variables that had a significant relationship with cholinestrase namely dose, amount, direction of spray, time, duration and frequency of spray. This is indicated by the significance value of the 6 independent variables is <0.05. Multivariate test results showed that there were 4 of the 7 independent variables that had a significant effect on cholinesterase ie dose, amount, time, and frequency of spray) (p<0.05) while the other 3 variables namely personal protective equipment, spray direction and duration had no significant effect . The most influential variable on colliniestarase is dose.